1994
DOI: 10.1271/bbb.58.2020
|View full text |Cite
|
Sign up to set email alerts
|

High Molecular Weight Protease in Rumen Ciliate Protozoa

Abstract: Mixed rumen ciliate protozoa (mainly Entodiniinae) from goats have two kinds of protease; one has a pH optimum of 3.0, the other is active at neutral or alkaline pH. The protease active at neutral or alkaline pH was partially purified from the supernatant after centrifugation of sonicated mixed rumen ciliate protozoa. The supernatant was chromatographed on Bio-Gel A-1.5 m and a partially purified protease was obtained. This protease had a molecular weight of more than 400,000. When the sonicated protozoa were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Trichomonas [24, 281, Trypanosomes [29], Dictyostelium [ 11. Acanthamoeba [30], Tetrahymena [31] and rumen ciliates [32]. The secretion of these cysteine proteases by protozoan parasites is thought to be responsible for specific host-parasite interactions related to their virulence ; attempts have been made to use these enzymes as potential targets for therapeutic intervention (for review see [3]).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomonas [24, 281, Trypanosomes [29], Dictyostelium [ 11. Acanthamoeba [30], Tetrahymena [31] and rumen ciliates [32]. The secretion of these cysteine proteases by protozoan parasites is thought to be responsible for specific host-parasite interactions related to their virulence ; attempts have been made to use these enzymes as potential targets for therapeutic intervention (for review see [3]).…”
Section: Discussionmentioning
confidence: 99%
“…Broderick et al (1988) indicated that free peptides originating from dietary protein degradation accumulate in the rumen, becoming available for protozoal attack. In the presence of protozoa, because of active protozoal peptidases (Newbold et al, 1989) and proteases (Naga and el-Shazly, 1968;Coleman, 1983;Forsberg et al, 1984;Nagasawa et al, 1994), dietary proteins and peptides are more susceptible to cleavage, which will release free AA into the medium. Moreover, Coleman (1975) proposed that protozoa utilize only about onehalf of their ingested N, the rest being expelled as shortchain peptides and free AA.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Broderick et al (1988) indicated that free peptides originating from dietary protein degradation might accumulate in the rumen and be available for protozoal attack, which might contribute to free TAA accumulation in the rumen. In the presence of RP because of active protozoal proteases (Naga and el-Shazly, 1968;Coleman, 1983;Forsberg et al, 1984;Nagasawa et al, 1994) and peptidases (Newbold et al, 1989), dietary proteins and peptides are more susceptible to cleavage, which will release free AA into the medium. Coleman (1975) proposed that RP utilize only about onehalf of their ingested N; the rest are expelled as shortchain peptides and free TAA.…”
Section: Methodsmentioning
confidence: 99%